Hubungan Pola Konsumsi Ultra Processed Food dengan Kadar Hemoglobin pada Remaja Putri - Alin Septiani; Lilik Hidayanti; Yana Listyawardhani (JURNAL RISET GIZI, 2025)
Background: Adolescent girls are the group most vulnerable to decreased hemoglobin (Hb) levels. The habit of consuming ultra-processed foods is thought to be one of the factors contributing to low hemoglobin levels in adolescent girls. Objective: This study aims to investigate the relationship between ultra-processed food (UPF) consumption patterns and hemoglobin (Hb) levels in adolescent girls. Methods: This study is an observational study using a cross-sectional design with 81 female students of SMP Negeri 2 Kota Tasikmalaya as subjects. The Hb level was measured using HemoCue® 201+. Pattern of UPF consumption (habits and amount of UPF consumption, as well as consumption of animal protein and heme iron from UPF) was measured using the SQ-FF. Data analysis used Spearman's Rank correlation and multiple linear regression modeling. Results: The mean Hb level of the subjects was 11.96 g/dL with an anemia incidence of 42%. The mean score of UPF consumption habits was 350. Statistical tests showed that UPF consumption habits (p=0.815), the amount of UPF consumption (p=0.906), animal protein consumption in UPF (p=0.743), and heme iron consumption in UPF (p=0.950) were not significantly related to hemoglobin levels. The results of multiple linear regression modeling showed that total animal protein consumption was the dominant factor related to subject Hb levels. Conclusion: The incidence of anemia among the subjects remains high. There is no significant relationship between UPF consumption and hemoglobin levels in adolescent girls. However, the selection of UPF types still needs to be considered in the formulation of adolescent diets.